2018
DOI: 10.1088/1674-1056/27/12/124101
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous transparent device and its layered realization

Abstract: Arbitrarily shaped electromagnetic transparent devices with homogeneous, non-negative, anisotropic and generic constitutive parameters are proposed based on linear transformation optics, which provides the flexibility for device design that is applicable for the practical fabrication. To remove the anisotropic property, a layered structure is developed based on effective medium theory. Simulation results show that with sufficient layers, the performance of the layered transparent device is nearly as perfect as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…A nationalized or regionalized database is an essential basis and premise for building life cycle assessment [35,[38][39][40]. Different countries and regions have established their own LCA databases and assessment tools for the construction industry [3,21,41].…”
Section: National/regionalized Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A nationalized or regionalized database is an essential basis and premise for building life cycle assessment [35,[38][39][40]. Different countries and regions have established their own LCA databases and assessment tools for the construction industry [3,21,41].…”
Section: National/regionalized Approachmentioning
confidence: 99%
“…They differ in terms of production conditions, electric mix, and relevant weight coefficients across countries and regions. Previous studies [38,39] have shown that a country-specific LCI database should be applied to obtain more referential results.…”
Section: National/regionalized Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Based on the form-invariant of Maxwell's equations and material interpretation, TO links both electromagnetic fields and media between the reference space and real space through the coordinate transformation. [9][10][11][12][13] The spatial beam bender designed by TO is often inhomogeneous and anisotropic, which is still challenging to realize. Choosing a suitable coordinate transformation can simplify the required materials.…”
Section: Introductionmentioning
confidence: 99%